Suppression of Host Innate Immune Response by Hepatitis C Virus via Induction of Autophagic Degradation of TRAF6 - Chan, Stephanie T. (J Virol, 2016)
Tumor necrosis factor receptor (TNFR)-associated factor 6 (TRAF6) is an important adaptor molecule that mediates the TNFR family and interleukin-1 (IL-1)/Toll-like receptor (TLR) signaling cascades. These pathways are important for the host to control viral infections. In this report, we demonstrated that hepatitis C virus (HCV) depleted TRAF6 from its host cells through a posttranslational mechanism. This depletion was independent of proteasomes, as it was not affected by the proteasome inhibitor MG132, but it was suppressed by bafilomycin A1, which led to the association of TRAF6 with autophagosomes. As bafilomycin A1 is a vacuolar ATPase inhibitor that inhibits autophagic protein degradation, these results suggested that HCV depleted TRAF6 via autophagy. The degradation of TRAF6 was apparently mediated by the p62 sequestosome protein, which is a factor important for selective autophagy, as it could bind to TRAF6 and its silencing stabilized TRAF6. The depletion of TRAF6 suppressed activation of NF-κB and induction of proinflammatory cytokines and enhanced HCV replication. In contrast, the overexpression of TRAF6 suppressed HCV replication. These results revealed a novel mechanism that was used by HCV to disrupt the host innate immune responses for viral replication and persistence. IMPORTANCE HCV can cause severe liver diseases and is one of the most important human pathogens. It establishes chronic infections in the great majority of patients that it infects, indicating that it has evolved sophisticated mechanisms to evade host immunity. TRAF6 is an important signaling molecule that mediates activation of NF-κB and expression of proinflammatory cytokines and interferons. In this study, we found that HCV infection suppressed the host innate immune response through the induction of autophagic degradation of TRAF6. This finding provided important information for further understanding how HCV evades host immunity to establish persistence.